Pengaruh Komposisi dan Lipatan Filter Udara Biokomposit Berbahan Ampas Tebu dan Sekam Padi terhadap Performa Mesin 4 Langkah 150cc - Muhammad Daniar Hidayat; Purwoko Purwoko; Ahmad Hanif Firdaus; Ratna Monasari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Internal combustion engines generate thermal energy through the combustion of an air-fuel mixture. The incoming air must be filtered, as it contains impurities and particles. While air filters are commonly made from paper, they can also be developed using organic waste materials such as sugarcane bagasse and rice husk. This study aims to analyze the effect of biocomposite air filters on engine power, torque, and specific fuel consumption (SFC), by varying the material composition and the number of pleats, and comparing the results with those of a standard air filter. The method used is a quantitative experimental approach involving dyno testing on a 150 cc motorcycle engine. The tested material compositions include 50:50, 40:60, 30:70, 60:40, and 70:30 (sugarcane bagasse\:rice husk), with pleat counts of 28, 26, and 24. Results showed that the biocomposite filter with 28 pleats and a 30:70 composition delivered the best performance, producing 18.47 Hp and 16.66 Nm of torque—higher than the standard filter’s 17.98 Hp and 15.52 Nm. In terms of fuel efficiency, the 26-pleat filter with a 50:50 composition recorded the lowest SFC at 41.90 g/kWh, significantly better than the standard filter’s 53.03 g/kWh. Conversely, the 60:40 composition resulted in the highest SFC due to increased airflow resistance.